Antiviral Activity of Arabinosyladenine and Arabinosylhypoxanthine in Herpes Simplex Virus-Infected KB Cells: Selective Inhibition of Viral Deoxyribonucleic Acid Synthesis in the Presence of an Adenosine Deaminase Inhibitor - Schwartz, Pauline M. (1976)
The antiviral activity of the fraudulent nucleoside arabinosyladenine (ara-A) against herpes simplex virus (HSV) type 1 was increased nearly 20-fold by the adenosine deaminase inhibitor, coformycin. The combination of ara-A plus coformycin was 90 times more potent in blocking HSV replication than was arabinosylhypoxanthine (ara-H). In suspension culture both drugs were more active than they were in monolayer culture. Deoxyribonucleic acid (DNA) synthesis also was inhibited by the nucleosides. Depending upon the species of DNA examined, ara-A was 8 to 15 times more active in the presence of coformycin, and the combination was 35 to 70 times more potent than ara-H. Both drugs inhibited total DNA synthesis to the same extent in uninfected and HSV-infected KB cells. In contrast, viral DNA synthesis was three to six times more susceptible to inhibition than was cellular DNA synthesis. Inhibition of viral DNA synthesis was more pronounced in suspension culture than in monolayer culture. However, the method of cell propagation did not alter the degree to which the drugs inhibited DNA synthesis in uninfected KB cells. An index has been derived to quantitate the extent of the selective inhibition of viral or cellular DNA synthesis. Fifty percent inhibitory concentrations of a drug were calculated for uninfected KB DNA synthesis and viral DNA synthesis and expressed as a ratio. The logarithm of this ratio was termed the selective index and was positive if viral DNA synthesis was inhibited preferentially or negative if uninfected KB DNA synthesis was more strongly inhibited. Data from experiments performed in monolayer culture gave positive selective index values of 0.3, 0.5, and 0.4 for ara-A plus coformycin, ara-A, and ara-H, respectively. Values of 0.7 and 0.6 were obtained from suspension culture data for ara-A plus coformycin and ara-H, respectively. Considered collectively, the data presented in this communication establish that coformycin increased the potency of ara-A but did not increase its selectivity.